Pengaruh Penerapan Permainan Susun Balok terhadap Kreativitas Anak Kelompok B di TK Samaturu Kecamatan Ranomeeto Kabupaten Konawe Selatan - Lestari, Sari Ari (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2016)
Preliminary studies when teaching in group A, especially in learning creativity, children learn to recognize symbols and circle images. But after being in group B, the child will be repeated again and continue the new lesson. In fact, when in group A children tend to be less enthusiastic. It can be seen that the child has not been able to draw a circle smoothly, then the child has not been able to draw a circle on their own. The purpose of the study was to determine the effect of the application of the block stacking game on the creativity of group B children at Samaturu Kindergarten, Ranomeeto District, South Konawe Regency in 2015. This type of research was a quasi-experimental with a two group pretest-posttest design. The study population was all children in Kindergarten B Samaturu, Ranomeeto District, Konawe Selatan Regency, in 2015 totaled 22 people. The number of intervention samples was 11 people and the control sample was 11 people. The sampling technique is total sampling. The statistical test used is the dependent t test. The results showed that there was an effect on the application of the block stacking game to the children of group B in Samaturu Kindergarten, Ranomeeto District, South Konawe Regency in 2015 (t-paired = 8.563 (p = 0.000). the application of the play method, so that the school becomes the right place for students to increase creativity.